1992
DOI: 10.1093/oxfordjournals.aje.a116198
|View full text |Cite
|
Sign up to set email alerts
|

Association of Smoking and Alcohol Drinking with Residential Fire Injuries

Abstract: To investigate whether tobacco, alcohol, and their combined use are important risk factors for fire injuries, the authors analyzed data from a population-based case-control study in King County, Washington, between 1986 and 1987. Cases (n = 116) were households with at least one fatal or nonfatal unintentional residential fire injury reported to the Washington State Fire Incident Reporting System from 1984 through 1985. Controls were selected by random digit dialing (n = 256). After adjustment for household si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 0 publications
2
45
0
Order By: Relevance
“…Of the 11 included studies,12–16 28–33 5 were case–control designs,12 13 29 30 33 2 were cross-sectional31 32 and 4 were classified by the review authors as statistical analyses of routinely collected data 14–16 28. Ten of the included studies were published papers12–16 28–30 32 33 and one was an unpublished thesis 31.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 11 included studies,12–16 28–33 5 were case–control designs,12 13 29 30 33 2 were cross-sectional31 32 and 4 were classified by the review authors as statistical analyses of routinely collected data 14–16 28. Ten of the included studies were published papers12–16 28–30 32 33 and one was an unpublished thesis 31.…”
Section: Resultsmentioning
confidence: 99%
“…It is likely that the association of fire-related mortality with maternal characteristics is mediated by behavioral and environmental factors; these include cigarette use, [17][18][19] alcohol consumption, 17,18,20 use of a space heater, 17,21 lack of a smoke detector, 17 and residence in a mobile home. 17 Of these factors, Runyan found that the greatest increase in risk of fire-related mortality was associated with lack of a smoke detector (odds ratio ϭ 3.4) and the presence of an alcoholimpaired person (odds ratio ϭ 7.5).…”
Section: Discussionmentioning
confidence: 99%
“…Logistic regression analysis ( Ballard et al , 1992 ;Marshall et al , 1998 ;Shai and Lupinacci, 2003 ) of both fi re incidence and fi re fatality was also undertaken, in order to ascertain whether a logistic regression approach might be more accu rate than a linear regression approach. The two values for logistic regression modelling of fi re fatalities were 0 = no fi re fatalities within an LSOA, and 1 = fi re fatalities within an LSOA.…”
Section: Comparison Of Calculated and Actual Unintentional Dwelling Fmentioning
confidence: 99%